What Makes Our Students Demotivated in Learning? - Crizjale V. Ahmad (Indonesian Journal of Educational Research and Technology, 2021)
This study aimed to determine the demotivating factors in learning. Thus, these students can be assisted in becoming successful in their studies. This study is only to determine the demotivating factors in learning of the Criminology students. The descriptive method of research was employed to determine the demotivating factors in the learning of Criminology students. The study was conducted at Notre Dame of Tacurong College (NDTC) with 90 respondents, of whom 72 were males and 18 females. Purposive sampling and statistical tools were utilized in the study. The results showed that the top three demotivating factors in learning are teachers lecture too much, students have difficulty in accomplishing classwork, and learning activities are not stimulating to hold their attention generally moderately demotivated them in their learning. Teachers play an essential role in motivating or demotivating students in learning. Other top demotivating factors are difficulties in accomplishing class works and classroom instruction. Then, learning activities are not stimulating to hold their attention. Also, all of which are teacher-related factors. It is recommended that the teachers moderately integrate other techniques to involve students in the discussion to prevent them from getting bored in the class. It is vital that students stay motivated to learn to succeed in their studies. This study is an approach to learn demotivating factors as an effort to improve students’ studies.